2017
DOI: 10.1371/journal.pone.0173332
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei modulates the immune system of Galleria mellonella and protects against Candida albicans infection

Abstract: Probiotics have been described as a potential strategy to control opportunistic infections due to their ability to stimulate the immune system. Using the non-vertebrate model host Galleria mellonella, we evaluated whether clinical isolates of Lactobacillus spp. are able to provide protection against Candida albicans infection. Among different strains of Lactobacillus paracasei, Lactobacillus rhamnosus and Lactobacillus fermentum, we verified that L. paracasei 28.4 strain had the greatest ability to prolong the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 48 publications
2
65
1
Order By: Relevance
“…In fermented with LUHS135, BC samples enterobacteria, E. coli and mould/yeast counts were reduced by 46.6%, 49.3% and 47.1%, respectively. L. paracasei can modulate the immune system and protect against candidiasis (Rossoni et al, 2017). In dried BC samples, LAB count ranged from 7.82 log 10 CFU g À1 (in the lyophilised and fermented with LUHS135 BC powder) to 6.00 log 10 CFU g À1 (in the vacuum-dried nonfermented BC powder).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fermented with LUHS135, BC samples enterobacteria, E. coli and mould/yeast counts were reduced by 46.6%, 49.3% and 47.1%, respectively. L. paracasei can modulate the immune system and protect against candidiasis (Rossoni et al, 2017). In dried BC samples, LAB count ranged from 7.82 log 10 CFU g À1 (in the lyophilised and fermented with LUHS135 BC powder) to 6.00 log 10 CFU g À1 (in the vacuum-dried nonfermented BC powder).…”
Section: Resultsmentioning
confidence: 99%
“…LAB are generally believed to play a positive role in maintaining good health and immune system in humans (Satpute et al, 2016). L. paracasei can modulate the immune system and protect against candidiasis (Rossoni et al, 2017). Antimicrobial activity of the Lactobacillus plantarum strain against Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, Salmonella enterica and Candida albicans has been demonstrated by Li et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Usually, in most experiments using larvae of G. mellonella, infection is induced by an intra hemocoelic injection of a titrated bacterial inoculum through the last left proleg. The response to infection can be assessed by different parameters: mortality, melanization, larvae mobility, cocoon formation, quantification of hemocytes and microorganisms in the hemolymph, alteration in gene expression and variations in the proteome [105][106][107]. Although the infection method and the scoring parameters used in microbial infection studies are very similar, there are numerous experimental variations: preparation or quantity of inoculum injected, source and management of larvae, experimental conditions or subjective interpretation of scoring parameters (morbidity or mortality).…”
Section: Limitationmentioning
confidence: 99%
“…paracasei X12 can block HT‐29 cell cycle and exhibit effective anticancer activities by modulation of mammalian target of rapamycin (mTOR) signalling pathway. Lactobacillus paracasei has shown to prevent Candida albicans infection by modulating the immune system (Rossoni et al ). In addition, it has been demonstrated that L. casei extract induced extrinsic apoptosis pathway in CT26 and HT29 cells by induction of TNF‐related apoptosis‐inducing ligand (TRAIL) (Tiptiri‐Kourpeti et al ).…”
Section: Resultsmentioning
confidence: 99%